Evaluation of shelf life of walnut kernel coated by antioxidants in combination with packaging under different storage conditions - Habashi, Roghieh Talebi; Zomorodi, Shahin; Talaie, Alireza; Jari, Sepideh Kalateh (Journal of Postharvest Technology, 2019)
The interaction effects of edible coating and packaging on Persian walnut kernel to extend shelf life by reducing oxidation and changing of  color were evaluated. Coating with chitosan (1%) in combination with thyme essential oil (TEO) at different concentrations (500 and 1000  μL/L) (CT500, CT1000) or chitosan alone (CT) in corporate with different packaging methods (Loose packaging, packaging in polypropylene bags  and Active packaging) (LP, PP, AP) compared with control walnut (C) were used. Storage conditions: (darkness; 55% RH, 4ºC and 45% RH,  25ºC). The results showed that amounts of L*, a*, b* values in treated samples decreased and samples which stored at 4ºC have acceptable  amount. The minimum moisture fluctuations in all packaging related to 4°C. The peroxide and conjugated diene values at 4°C were lower amount. Treatments did not have positive effect on free fatty acids of walnut kernels.
Keywords: Antioxidants; Packaging; Shelf life; Walnut